The Syntax-Semantics Interface Of Copular Constructions: Evidence From Standard Arabic - Al-Horais, Nasser (Ijaz Arabi Journal of Arabic Learning, 2025)
This paper aims to provide additional supporting evidence for the Equative Approach by reducing the taxonomy of copular clauses into just two categories: predicational and equative. Data from copular structures in Standard Arabic are presented to bolster this approach. These data reveal that Standard Arabic features two distinct lexical copulas: (1) an inflected verbal copula, "kaana," and (2) a pro copula. A detailed examination of these two copular structures shows that the verbal copula is exclusively utilized in predicational clauses. In contrast, the pro copula is designated explicitly for equative clauses. This delineation indicates that the semantics of copular constructions cannot be adequately captured solely by the single-be analysis advocated by the Inverse Approach. Instead, an approach positing two copulas, one for prediction and one for equation, is deemed necessary, thereby advocating for the equivalent approach.